A sodium vanadium fluorophosphate electrode material and its ball milling preparation method and application
Through step-by-step ball milling method and coating technology of dopamine hydrochloride and carbon nanotubes, excellent performance vanadium fluorophosphate sodium electrode material was prepared, which solved the shortcomings of existing NVPF materials in terms of rate performance and conductivity, and achieved more efficient sodium ion transport.
Patent Information
- Application Number
- CN202310362530.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-07
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-04-07
AI Technical Summary
The existing sodium ion battery positive electrode material NVPF has shortcomings in rate performance and conductivity. The traditional one-step coating method has resulted in uneven coating thickness, many defects and impurities, and cannot effectively improve the performance of the material.
The step-by-step ball milling method is used to prepare the sodium vanadium phosphate electrode material, and the precursor is formed through a single ball mill, and then the secondary ball mill is coated with dopamine hydrochloride and carbon nanotubes to form a carbon coated material with irregular mesh structure.
It realizes uniform coating of the material surface, enhances electron transport capability, improves the rate performance and conductivity of the material, and improves the transportation efficiency of sodium ions.
Smart Images

Figure CN116504965B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of material preparation, and specifically relates to a sodium vanadium fluorophosphate electrode material and a ball milling preparation method and application thereof. Background Art
[0002] Sodium-ion batteries have many advantages such as low cost and high safety, but they still have disadvantages such as poor rate performance, low cycle stability, low energy density and poor reversible capacity. Therefore, there is an urgent need to develop sodium-ion batteries with excellent performance and low cost, among which the positive electrode material is the key part.
[0003] There are three common positive electrode materials for sodium-ion batteries, namely layered transition metal oxides, Prussian blue analogs, and polyanion compounds. The three sodium-ion battery positive electrode materials each have their own advantages and disadvantages. The cycle life and stability of layered transition metal oxides are poor; the cyanide of Prussian blue analogs is potentially toxic; and the energy density of polyanion compounds is poor. As one of the polyanion compounds, how to improve the energy density of NVPF is currently the top priority of discussion.
[0004] At present, common modification methods include carbon coating and element doping (Na+ doping, V doping, anion doping). For carbon coating, carbon coating can improve the electron transport ability of the surface of NVPF particles and increase the number of active sites.
[0005] The commonly used method at present is the one-step coating method. Although this method is more convenient and faster than the step-by-step coating method, in the process of one-step coating, the NVPF particles cannot be fully and evenly contacted with the carbon source, and inevitably there will be problems such as uneven coating thickness, many defects and impurities, low coverage, and uneven particle size. It is impossible to improve the material's rate performance and conductivity. For element doping, it is to improve the electron transmission capacity of the internal structure of NVPF, but currently more about V-site doping, while there are relatively few literatures on Na+-site doping and anion doping, which still needs further expansion and research.
[0006] In view of this, this application is hereby filed. Summary of the invention
[0007] In order to solve one of the above technical defects, the embodiments of the present application provide a sodium vanadium fluorophosphate electrode material and a ball milling preparation method and application thereof.
[0008] The technical solution of the present application provides a method for preparing sodium vanadium fluorophosphate electrode material, which adopts a step-by-step ball milling method; the method comprises the following steps:
[0009] Sodium fluoride, a vanadium source, a phosphorus source, and a reducing agent are added into a ball mill according to a certain ratio, and a mixture of a certain amount of acetonitrile and anhydrous ethanol is used as a dispersant to perform a ball milling for a preset time to obtain a precursor;
[0010] Adding the carbon nanotube dispersion and dopamine hydrochloride dissolved in tris buffer into a ball mill according to a preset ratio for secondary ball milling for a preset time, and grinding to obtain a solid material after drying;
[0011] The obtained fixed material is calcined in a tube furnace, and after natural cooling, a carbon-coated sodium vanadium fluorophosphate electrode material is obtained.
[0012] Preferably, the sodium fluoride, vanadium source, phosphorus source and reducing agent are added to the ball mill in a molar ratio of 6:4:4:3; the volume ratio of acetonitrile and anhydrous ethanol is 1:9; and the volume ratio of the precursor, dopamine hydrochloride buffer and carbon nanotube dispersion is 5:1:1.
[0013] Preferably, the ball mill is a zirconia ball mill.
[0014] Preferably, the loading amount and ball loading amount of the ball mill shall not exceed one third of the volume of the ball mill body.
[0015] Preferably, both the primary ball milling and the secondary ball milling are performed in an intermittent working mode.
[0016] Preferably, the speed of the first ball milling is 600 r / min and the ball milling time is 12 h;
[0017] The rotation speed of the secondary ball milling is 600r / min and the ball milling time is 1h to 3h.
[0018] Preferably, the calcination conditions in the tubular furnace are: in an argon environment, the temperature is increased to 350° C. at a heating rate of 5° C. / min and maintained for 5 h, and then increased to 750° C. at a heating rate of 5° C. / min and maintained for 8 h.
[0019] Preferably, the technical solution of the present application provides a sodium vanadium fluorophosphate electrode material for preparing a positive electrode material, wherein the positive electrode material is composed of Super-P, CMC and sodium vanadium fluorophosphate electrode material; the mass ratio of Super-P, CMC and sodium vanadium fluorophosphate electrode material is 7:2:1.
[0020] The technical solution of the present application also provides a sodium vanadium fluorophosphate electrode material. Compared with the sodium vanadium fluorophosphate electrode material prepared by other methods, the morphology of the sodium vanadium fluorophosphate electrode material is distributed between carbon nanotubes according to the structure of particles or layers, presenting an irregular network structure. The surface of the material is uniformly coated with a carbon layer rich in nitrogen atoms converted from polydopamine, and the nitrogen atoms exist in the form of pyridinic nitrogen, pyrrolic nitrogen and graphitic nitrogen.
[0021] Beneficial effects of this application:
[0022] 1. This application innovatively uses dopamine hydrochloride and carbon nanotubes as carbon sources to coat NVPF, and uses a step-by-step ball milling coating method to replace the traditional one-step coating method. This method is to disperse a certain amount of dopamine hydrochloride in a tris buffer solution, and then configure a certain amount of carbon nanotube dispersion. The above two solutions and NVPF are added to a ball mill for secondary ball milling, so that each NVPF can be evenly coated with PDA and CNTs and connected to each other through carbon nanotubes to construct a three-dimensional conductive network. The coated material is then calcined under an argon atmosphere to obtain NVPF@PDA@CNTs. A uniform carbon layer can be coated on the surface of the material. The coating method is simple and suitable for expansion. By adjusting the concentration of dopamine hydrochloride, the amount of carbon nanotubes and the ball milling time, the thickness of the carbon layer can be accurately controlled, the particle size can be controlled, the specific surface area of the material can be increased, and the inherent rate performance and poor conductivity of the material can be improved.
[0023] 2. The present application adopts a step-by-step ball milling coating method to first mix acetonitrile and anhydrous ethanol as a dispersant for the first ball milling. Different from the common dry ball milling or wet ball milling with anhydrous ethanol as a dispersant, acetonitrile has better solvent properties than ethanol and can be infinitely miscible with water and alcohols. The mixture of the two can better disperse the various drugs in the ball mill, prevent the sedimentation and aggregation of particles, and enable them to react more fully to form a relatively stable dispersion system using ball milling; then a secondary ball milling reaction is carried out, and dopamine and carbon nanotubes can be formed alternately under high-speed rotation, thereby forming an irregular network structure of dopamine and carbon nanotubes mixed and coated on the NVPF surface, connecting the NVPF particles through a 3D network structure, thereby enhancing the transmission of electrons between NVPF particles; this structure can effectively suppress the size of the grains and improve the conductivity of the material, thereby increasing its ion diffusion rate.
[0024] 3. This application adopts secondary ball milling and then high-temperature sintering to form a carbon layer with uniform thickness, and the thickness of the carbon layer can be controlled according to needs by adjusting the concentration of dopamine hydrochloride, the amount of carbon nanotubes used and the ball milling time.
[0025] 4. The present application uses dopamine hydrochloride and carbon nanotubes to carbon-coat NVPF. Dopamine hydrochloride will disperse and release dopamine in tris buffer. Since dopamine can self-aggregate on almost any surface, it will form an irregular network structure with carbon nanotubes under high-speed ball milling, in which the two are alternately coated on the surface of NVPF. The NVPF particles are connected through 2D and 3D network structures to build a conductive framework between particles, thereby accelerating the transmission of electrons between NVPF particles. In addition, since the carbon layer converted from polydopamine is N-doped carbon, the N atoms are derived from the amino groups of dopamine. Nitrogen doping in the carbon layer can produce additional active sites to further increase the capacity and improve the conductivity of the material, and shorten the migration path of Na+ during the charge and discharge process. In addition, since the carbon layer converted from polydopamine is N-doped carbon, nitrogen doping in the carbon layer can produce additional active sites to further increase the capacity and improve the conductivity of the material, and shorten the migration path of Na+ during the charge and discharge process. + Migration paths during charge and discharge.
[0026] 5. The synthesis method provided in this application is easy to operate, time-saving and has the potential for large-scale production. It uses acetonitrile and anhydrous ethanol as dispersants for wet ball milling, which can effectively avoid the uneven reaction caused by solid-solid contact. In addition, since dopamine has good film-forming properties, it can effectively protect NVPF from being corroded by the electrolyte, and carbon nanotubes have good conductivity and excellent mechanical properties, which can shorten the conductive path between particles. The combination of the two can improve the cycle life of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0028] Figure 1 This is a spectrum of NVPF@PDA@CNTs prepared in the examples of this application;
[0029] Figure 2 This is the rate performance diagram of NVPF@PDA@CNTs of the embodiment of this application;
[0030] Figure 3 This is the cycling performance diagram of NVPF@PDA@CNTs prepared in the examples of this application.
[0031] Figure 4 This is the SEM image of NVPF@PDA@CNTs prepared in the examples of this application.
[0032] Figure 5 This is the TEM image of NVPF@PDA@CNTs prepared in the example of this application. DETAILED DESCRIPTION
[0033] In order to make the technical solutions and advantages in the embodiments of the present application more clearly understood, the exemplary embodiments of the present application are further described in detail below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present application, rather than an exhaustive list of all the embodiments. It should be noted that the embodiments in the present application and the features in the embodiments can be combined with each other without conflict.
[0034] The embodiment of the present application provides a method for preparing a sodium vanadium fluorophosphate electrode material, which adopts a step-by-step ball milling method; the method comprises the following steps:
[0035] Sodium fluoride, a vanadium source, a phosphorus source, and a reducing agent are added into a ball mill according to a certain ratio, and a mixture of a certain amount of acetonitrile and anhydrous ethanol is used as a dispersant to perform a ball milling for a preset time to obtain a precursor;
[0036] Adding the carbon nanotube dispersion and dopamine hydrochloride dissolved in tris buffer into a ball mill according to a preset ratio for secondary ball milling for a preset time, and grinding to obtain a solid material after drying;
[0037] The obtained fixed material is calcined in a tube furnace, and after natural cooling, a carbon-coated sodium vanadium fluorophosphate electrode material is obtained.
[0038] As a specific embodiment of the present application, a method for preparing a sodium vanadium fluorophosphate electrode material is provided, wherein the sodium fluoride, vanadium source, phosphorus source, and reducing agent are added to a ball mill in a molar ratio of 6:4:4:3; the volume ratio of acetonitrile and anhydrous ethanol is 1:9; and the volume ratio of the precursor, dopamine hydrochloride buffer, and carbon nanotube dispersion is 5:1:1.
[0039] As a specific embodiment of the present application, a method for preparing a sodium vanadium fluorophosphate electrode material is provided, wherein the ball mill is a zirconium oxide ball mill.
[0040] As a specific embodiment of the present application, a method for preparing sodium vanadium fluorophosphate electrode material is provided, and the loading amount and ball loading amount of the ball mill jar shall not exceed one third of the volume of the ball mill jar.
[0041] As a specific embodiment of the present application, a method for preparing sodium vanadium fluorophosphate electrode material is provided, in which both the primary ball milling and the secondary ball milling are performed in an intermittent working mode.
[0042] As a specific embodiment of the present application, a method for preparing a sodium vanadium fluorophosphate electrode material is provided, wherein the speed of the first ball milling is 600 r / min and the ball milling time is 12 h;
[0043] The rotation speed of the secondary ball milling is 600r / min and the ball milling time is 1h to 3h.
[0044] As a specific embodiment of the present application, a method for preparing a sodium vanadium fluorophosphate electrode material is provided. The tubular furnace calcination conditions are as follows: in an argon environment, the temperature is increased to 350°C at a heating rate of 5°C / min and maintained for 5 hours, and then increased to 750°C at a heating rate of 5°C / min and maintained for 8 hours.
[0045] As a specific embodiment of the present application, a method for preparing a sodium vanadium fluorophosphate electrode material is provided, which is used to prepare a positive electrode material, wherein the positive electrode material is composed of Super-P, CMC and a sodium vanadium fluorophosphate electrode material; the mass ratio of the Super-P, CMC and the sodium vanadium fluorophosphate electrode material is 7:2:1.
[0046] As a specific embodiment of the present application, a method for preparing a sodium vanadium fluorophosphate electrode material is provided.
[0047] S1: First, weigh 0.63g of sodium fluoride, 1.17g of ammonium metavanadate, 1.15g of ammonium dihydrogen phosphate and 1.441g of citric acid, and add the above materials into a zirconia ball mill at the same time, and mix the balls in a ratio of 10%:30%:60% for large balls: medium balls: small balls. The loading amount and the loading amount of balls shall not exceed one-third of the volume of the ball mill, respectively. A mixture of acetonitrile and anhydrous ethanol is used as a dispersant in a ratio of 10%:90% for ball milling. In addition, since mechanical energy will be converted into heat energy during the ball milling process, the temperature in the ball mill will increase. Therefore, an intermittent working mode (working for 20 minutes and pausing for 5 minutes) is adopted to ball mill at a speed of 600r / min for 12 hours.
[0048] S2: Dissolve 1.212 g of dopamine hydrochloride powder in tris buffer (pH=8.5-8.8), and fully disperse it in the tris buffer by ultrasonic treatment at 25°C for 40 minutes. Then add a certain amount of prepared carbon nanotube dispersion into the ball mill, and continue ball milling for 2 hours at a speed of 600 r / min in an intermittent working mode (work for 20 minutes and pause for 5 minutes) according to the ratio of precursor: dopamine hydrochloride buffer: carbon nanotube dispersion of 5:1:1.
[0049] S3: The NVPF@PDA@CNTs obtained in S2 were transferred to a drying oven and dried at 80°C for 12 hours. The dried material was then placed in an agate mortar and ground for 30 minutes. The ground material was placed in a tubular furnace and heated to 350°C at a rate of 5°C / min and maintained for 5 hours in an argon environment (hydrogen 5% argon 95%). The purpose was to remove residual moisture and ammonia in the NVPF@PDA@CNTs. The temperature was then raised to 750°C at a rate of 5°C / min and maintained for 8 hours. After naturally cooling to room temperature, the final carbon-coated sodium vanadium fluorophosphate positive electrode material (NVPF@PDA@CNTs) was obtained.
[0050] S4: The positive electrode is composed of NVPF@PDA@CNTs, Super-P, and CMC in a ratio of 7:2:1. The separator is made of glass fiber, the current collector is made of aluminum foil, the negative electrode is made of sodium sheet, the electrolyte is 1MNaClO4, the solvent is a mixture of EC and DEC (mass ratio 1:1), and the additive is 2% FEC by mass. The button cell is assembled in a glove box with an argon atmosphere.
[0051] like Figure 1 The figure shows the spectrum of NVPF@PDA@CNTs prepared in step S3. The structure of the composite material was characterized by XRD test. The diffraction peaks of the composite material are basically consistent with the results reported in the literature, and form a good correspondence with the standard NVPF standard card. This shows that the NVPF@PDA@CNTs sample prepared by the secondary high-energy ball milling method has good crystallinity.
[0052] like Figure 2 As shown, it is the rate performance diagram of NVPF@PDA@CNTs prepared in step S3; 。 At current densities of 1C, 2C, 5C, and 10C, NVPF@PDA@CNTs can release 112.31, 109.52, 102.35, and 95.18 mAh·g, respectively. -1 Even at a rate of 10C, NVPF@PDA@CNTs can still show a reversible capacity of 95.18 mAh g -1 The high capacity indicates that the material has good rate performance.
[0053] like Figure 3 As shown in the figure, it is the cycle performance diagram of NVPF@PDA@CNTs prepared in step S3; the first cycle coulomb efficiency of the prepared material is 94%, mainly because the electrolyte and the prepared material show that the formation of SEI film will lose some sodium ions. In the subsequent charge and discharge process, the coulomb efficiency is close to 100%, and after 200 cycles, the capacity retention rate at 1C rate is 91.3%, and the capacity can reach 107mAhg-1 It has good capacity retention and cycle performance.
[0054] like Figure 4 As shown, it is the SEM image of NVPF@PDA@CNTs prepared in step S3; it can be seen from the figure that the NVPF@PDA@CNTs material is irregularly layered and granular, and is evenly distributed in the 3D conductive network structure of carbon nanotubes. The particle size can be reduced by segmenting the carbon nanotubes. The average particle size of NVPF@PDA@CNTs particles is about 2um, which increases the specific surface area of the material and is conducive to the transportation of sodium ions. However, due to the agglomeration of particles during the high-temperature synthesis process of the solid phase method, agglomeration still occurs.
[0055] like Figure 5 As shown, it is the TEM image of NVPF@PDA@CNTs prepared in step S3; the material obtained after high-temperature sintering shows that a carbon layer with uniform thickness will be formed, and the formed carbon layer can effectively prevent the contact between the active material and the electrolyte, thereby improving the stability of the material. In addition, the coating method is simple and easy to expand. The thickness of the carbon layer can be accurately controlled by adjusting the concentration of dopamine hydrochloride, the amount of carbon nanotubes and the ball milling time, and the particle size can be controlled, thereby improving the inherent characteristic of poor conductivity of the material.
[0056] In summary, the method of synthesizing sodium vanadium fluorophosphate-carbon composite positive electrode material by high-energy ball milling has the advantages of convenience, simplicity, easy scale-up, and environmental friendliness. The obtained material has a capacity retention rate of 91.3% at a 1C rate after 200 cycles, and the capacity can reach 107.51 mAhg -1 At a rate of 10C, its capacity can reach 95.18 mAhg -1 , with excellent cycle performance and rate performance.
[0057] It is worth noting that the method of synthesizing NVPF by using the coating strategy of dopamine hydrochloride and carbon nanotubes proposed in this application, the method of using a mixture of acetonitrile and ethanol as a dispersant, and the secondary coating method using ball milling are all protected by patents.
[0058] It is worth noting that the technical steps S1-S5, experimental dosage, experimental materials, ball milling time, ball milling speed, dopamine hydrochloride dosage, carbon nanotube dosage, heating temperature, heating time, etc. in this application, including but not limited to the innovative details of the above contents, are all within the scope of patent protection.
[0059] Although the preferred embodiments of the present application have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications falling within the scope of the present application.
[0060] Obviously, those skilled in the art can make various changes and modifications to the present application without departing from the spirit and scope of the present application. Thus, if these modifications and variations of the present application fall within the scope of the claims of the present application and their equivalents, the present application is also intended to include these modifications and variations.
Claims
1. A method for preparing sodium vanadium fluorophosphate electrode material, characterized in that: The step-by-step ball milling method is adopted; the steps include: Sodium fluoride, vanadium source, phosphorus source and reducing agent are added into a ball mill according to a certain proportion, and a mixture of a certain amount of acetonitrile and anhydrous ethanol is used as a dispersant to perform a ball milling for a preset time to obtain a precursor; the speed of the ball milling is 600 r / min, and the ball milling time is 12 h; The carbon nanotube dispersion and dopamine hydrochloride dissolved in tris buffer are added into the ball mill according to a preset ratio for secondary ball milling for a preset time, and then dried and ground to obtain a solid material; the volume ratio of the precursor, dopamine hydrochloride buffer and carbon nanotube dispersion is 5:1:1; the rotation speed of the secondary ball milling is 600r / min, and the ball milling time is 1h~3h; The obtained solid material is calcined in a tube furnace, and after natural cooling, a carbon-coated sodium vanadium fluorophosphate electrode material is obtained; the tube furnace calcination conditions are: in an argon environment, the temperature is increased to 350°C at a heating rate of 5°C / min and maintained for 5 hours, and then increased to 750°C at a heating rate of 5°C / min and maintained for 8 hours; The sodium vanadium fluorophosphate electrode material is distributed between carbon nanotubes in a particle or layer structure, presenting an irregular network structure, and the surface of the material is evenly coated with a carbon layer rich in nitrogen atoms converted from polydopamine, wherein the nitrogen atoms exist in the form of pyridinic nitrogen, pyrrolic nitrogen and graphitic nitrogen.
2. The preparation method according to claim 1, characterized in that The sodium fluoride, vanadium source, phosphorus source and reducing agent are added into the ball mill in a molar ratio of 6:4:4:3; the volume ratio of acetonitrile and anhydrous ethanol is 1:
9.
3. The preparation method according to claim 1 or 2, characterized in that: The ball mill is a zirconia ball mill.
4. The preparation method according to claim 1, characterized in that: The loading amount and ball loading amount of the ball mill shall not exceed one third of the volume of the ball mill.
5. The preparation method according to claim 1, characterized in that: Both the primary ball mill and the secondary ball mill are operated in an intermittent working mode.
6. An application of sodium vanadium fluorophosphate electrode material, characterized in that: The sodium vanadium fluorophosphate electrode material prepared by the preparation method according to any one of claims 1 to 5 is used to prepare a positive electrode material, wherein the positive electrode material consists of Super-P, CMC and sodium vanadium fluorophosphate electrode material; the mass ratio of Super-P, CMC and sodium vanadium fluorophosphate electrode material is 7:2:1.
Citation Information
Patent Citations
Preparation method of high-performance ionic liquid modified sodium vanadium phosphate / carbon composite cathode material
CN107093716A
Sodium vanadium phosphate electrode material of vanadium-site copper-doped composite carbon nano tube and preparation method and application of sodium vanadium phosphate electrode material
CN113659139A
Composite positive plate containing single-crystal high-nickel positive electrode material and all-solid-state battery
CN114551791A
Transition metal phosphate sodium ion battery positive electrode material and preparation method and application thereof
CN115036477A